2021
DOI: 10.3390/s21248294
|View full text |Cite
|
Sign up to set email alerts
|

Feature Fusion of a Deep-Learning Algorithm into Wearable Sensor Devices for Human Activity Recognition

Abstract: This paper presents a wearable device, fitted on the waist of a participant that recognizes six activities of daily living (walking, walking upstairs, walking downstairs, sitting, standing, and laying) through a deep-learning algorithm, human activity recognition (HAR). The wearable device comprises a single-board computer (SBC) and six-axis sensors. The deep-learning algorithm employs three parallel convolutional neural networks for local feature extraction and for subsequent concatenation to establish featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Therefore, the performance results of the investigated model will highly depend on the data in the testing set. In order to avoid this problem, similar to [18,22,25,27], we applied the k-fold cross validation, where k is set to 10, to the experiments. The 10-fold cross validation will divide a dataset into 10 parts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the performance results of the investigated model will highly depend on the data in the testing set. In order to avoid this problem, similar to [18,22,25,27], we applied the k-fold cross validation, where k is set to 10, to the experiments. The 10-fold cross validation will divide a dataset into 10 parts.…”
Section: Methodsmentioning
confidence: 99%
“…In the second category, we apply a set of sensor data to a multi-branch DL architecture where each branch uses a different DL model and results in a different set of features. Three-branch DL architectures were proposed in [20,21,[24][25][26][27][28], where a CNN model [20,24,27,28], a hybrid of a CNN model, and a bidirectional long short-term memory (LSTM) layer [25], as well as a CNN model with an SE block [21], and a hybrid of convolutional layers and gated recurrent unit (GRU) layers [26] were used on each branch to extract a set of features. The differences among these branches are the kernel sizes of the convolutional layers [20,21,[24][25][26][27][28] and the number of layers [20].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Pardo et al placed sixaxis sensors on participant wrists and waists for data collection and used a CNN to classify four shots in tennis and seven non-tennis activities with a mean accuracy of 99% [24]. Yen et al used deep learning with feature fusion method into wearable sensor devices for human activity recognition and the accuracies in tenfold cross-validation were 99.56% and 97.46%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently become possible to extract features from raw sensory data using deep learning methods. On the other hand, the most recent research in HAR has shown that one cannot disregard the significance of handcrafted features because this information is derived from the domain expertise of specialists [3]. Conventional ways of machine learning extract hand-crafted features that need to be chosen manually.…”
Section: Introductionmentioning
confidence: 99%